Implementation of Human Resource Management in the Adaptation Period for New Habits - E. Nurzaman AM; Azhar Affandi; Andiyanga Udobong; Sarwani Sarwani; hernawan hernawan (Har Press Indonesia, 2020)
The COVID-19 pandemic has disrupted the global economy and business, and Human Resources (HR) is at its heart. With the organization now on the cusp of recovery, the role of HR has become even more important. The question is not limited in terms of imagining the impact and role of human resources in the future post-COVID-19. One thing is certain - the pandemic and its inherent effects on business have highlighted the need for adaptability and resilience in today's workforce, accelerated the shift towards a new digital economy, and emphasized the importance of HR in the new normal. This study tries to describe the role of human resource management in an effort to restore organizational performance. This study is a qualitative research using descriptive methods to describe the object under study. The results showed that the role of HRM during the COVID-19 pandemic was very strategic, especially in terms of maintaining the health and safety of workers when returning to work by implementing strict health protocols and also providing guidance and assistance for employees affected by COVID-19 such as downsizing and restructurisation. This research also presents HR transformation in terms of employee performance appraisal using results-based performance methods and the use of technology as a support in job optimization